2003
DOI: 10.1097/00041433-200306000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of HDL regulation in humans

Abstract: Disorders affecting HDL metabolism are complex because monogenic disorders causing low HDL do not necessarily correlate with premature vascular disease. To date, pathologic phenotypes have only been deduced among several HDL candidate genes. Understanding the genetic underpinnings associated with variant HDL and reverse cholesterol transport provides an exceptional opportunity to identify novel agents that may optimize this process and reduce vascular event rates beyond currently available LDL lowering therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 72 publications
1
50
0
1
Order By: Relevance
“…Moreover, pitavastatin promoted the expression of HDL metabolism-associated proteins such as APOA1. It is proposed that this is probably via enhancement of PPAR expression, since APOA1 and ABCA1 expression are upregulated by PPAR agonists [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pitavastatin promoted the expression of HDL metabolism-associated proteins such as APOA1. It is proposed that this is probably via enhancement of PPAR expression, since APOA1 and ABCA1 expression are upregulated by PPAR agonists [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several LPL SNPs have been associated with HDL-C (Table 1) (Ahn et al, 1993;Corella et al, 2002;Holmer et al, 2000;Klos and Kullo, 2007;Klos et al, 2006;Komurcu-Bayrak et al, 2007;Lee et al, 2004;Nettleton et al, 2007;Senti et al, 2001;Wittrup et al, 1999); however, many of them are in strong linkage disequilibrium with each other (e.g., rs320, rs326, rs13702, rs10105606) (Boes et al, 2009;Heid et al, 2008). Hepatic lipase (HL; LIPC) is a glycoprotein that is synthesized by liver cells (hepatocytes) and catalyzes the hydrolysis of TG and phospholipids (Miller et al, 2003). For example, after hydrolysis of TG by LPL, VLDL particles are reduced to IDL particles and can be further hydrolyzed by HL/LIPC to LDL or taken up by the liver (Kwan et al, 2007).…”
Section: Genetic Variation In Enzymes Involved In Lipid Metabolism Anmentioning
confidence: 99%
“…Scavenger receptor class B, type 1 (SCARB1; SR-B1), which is highly expressed in liver and steroidogenic tissues (testes, ovaries, adrenal) (Cao et al, 1997), has been shown to participate in the uptake of HDL in animals by transferring cholesterol from the HDL-C particle and releasing the lipid-depleted HDL particle into the circulation (Acton et al, 1996;Miller et al, 2003). The human SCARB1 gene is located on chromosome 12 (12q24.31).…”
Section: Genetic Variation In Receptors and Transporters And Hdl-c Lementioning
confidence: 99%
See 2 more Smart Citations